Trafficking in persons - Orhant, Melanie ([ ] [ ])
Discusses the issue of trafficking generally, describes the difficulties that organisation face when trying to assist trafficked persons; reviews a number of solutions, and outlines what public health workers can do in their daily work to help trafficked persons.